1985
DOI: 10.1104/pp.77.3.770
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Amino Acids and Other Organic Compounds by Lemna paucicostata Hegelm. 6746

Abstract: A survey of the capacity of Lemna paucicostata to take up organic compounds such as might be present in the natural environment of this plant has identified eight discrete transport systems. Reciprocal inhibition studies defined the preferred substrates for these systems as follows: (a) neutral L-a-amino acids, (b) basic amino acids, (c) purine bases, (d) choline, (e) ethanolamine, (f) tyramine, (g) urea, and (h) aldohexoses. Each of these systems takes up its preferred substrates at high rates. At low concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…[ relative to that of L-serine itself (770 nl/frond min [6]). Paper chromatography (solvent B) or electrophoresis at pH 7.0 of aliquots of the methanol-water-soluble fractions showed that all of the tissue radioactivity moved with serine, none with Pserine.…”
Section: U(m -T) Tmentioning
confidence: 99%
See 1 more Smart Citation
“…[ relative to that of L-serine itself (770 nl/frond min [6]). Paper chromatography (solvent B) or electrophoresis at pH 7.0 of aliquots of the methanol-water-soluble fractions showed that all of the tissue radioactivity moved with serine, none with Pserine.…”
Section: U(m -T) Tmentioning
confidence: 99%
“…Initial rates of uptake of P-serine were measured over 5 to 20 min periods as described (6). Other Methods Chromatographic systems and solvents previously designated as A through E were used as described (32) of radioactivity in particular compounds which had been subjected to several sequential purification steps have been described (7,8,31,32 ,32P]GP-EA was assumed to have come into isotopic equilibrium) were used to calculate the "'C specific radioactivity (dpm/nmol) of the ['C,`2P]GP-EA.…”
Section: Uptakesmentioning
confidence: 99%
“…In a recent survey of the capacity of Lemna paucicostata to take up organic compounds, it was found that this plant possesses specific and distinct systems for the transport of eight groups of organic compounds (4). Among these is a system which transports ethanolamine, and another which transports choline.…”
mentioning
confidence: 99%
“…velocity . substrate concentration) (4), in units of nl/frond-min. Frond-d, calculated as described (1), was multiplied by 1440 to obtain frond-min.…”
mentioning
confidence: 99%
See 1 more Smart Citation